Word of mouth effectiveness in medical tourism services - ميمونة, حجاب (جامعة المسيلة, 2021)
The word-of-mouth becaming very effective in the medical tourism and markiting, where it became a diffuse style in attracting customers. This study aims to demonstrate the effectiveness of the word-of-mouth at the services of the medical tourism in the Baraka as a study sample. And for evaluate this study, a questionnaire was directed to the visitors to this tourist complex, it was analyzed by SPSS. A high positive rating was assumed by costomers on the effectiveness of the word-of-mouth on the reputation of the El Baraka midical tourism complex. Ultimately based onthe findings the general hypothesiswas accepted, consequently the Word of mouth is very effective for El Baraka midical tourism complex.
- A case study of el Baraka complex at Guelma state
Keywords: Word-of-mouth, Medical Tourism,Destination, Midical tourists; Word-of-mouth, Medical Tourism,Destination, Midical tourists